(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In Permjakova Alexander Anatoljevicha and Porohnenko Alexander Vasiljevicha’s clause «Formation of a healthy way of life of schoolboys» is considered the conceptual device, the factors influencing formation of a healthy way of life of schoolboys, a way of formation of a healthy way of life of schoolboys.